PRESENTISM AND SOCIOECONOMIC ASPECTS IN DOCTORS OF A PSYCHIATRIC HOSPITAL: PRESENTISMO Y ASPECTOS SOCIOECONÓMICOS EN MÉDICOS DE UN HOSPITAL PSIQUIÁTRICO - Miraval Rojas, Edgar Jesus (2019)
Objectives: Determine the relationship between presenteeism and socioeconomic aspects in doctors of the Hospital Nacional Víctor Larco Herrera in 2018. Methods: A non-experimental, cross-sectional, correlational, prospective quantitative study was carried out. 60 doctors from the Hospital Nacional Víctor Larco Herrera were included, the dependent variable was occupational presenteeism, measured with the Stanford SPS- 6 work presenteeism scale, the independent variables were the socioeconomic aspects. For the bivariate analysis, the Pearson correlation test was used, obtaining the correlation coefficient (r) and the p value. Results: 54.5% of the sample were female, the most frequent age group was 28 to 37 years old with 45.5%. The prevalence of presenteeism was 49 (81.8%). It was significantly associated to the labor condition (r = -0.236, value p = 0.039), correlating with having a contracted or third-party regime against permanent contract worker. There was no statistically significant association with having another job, people who depend economically, work hours and years of service. Conclusion: The presenteeism in doctors of the Larco Herrera National Hospital was associated to the labor condition. It is recommended to carry out more studies in this regard in order to better understand the reality of this problem in our country.